Coordination in service value networks: A mechanism design approach - Benjamin Blau (KIT Scientific Publishing, 2009)
The fundamental paradigm shift from traditional value chains to agile service value networks (SVN) implies new economic and organizational challenges. This work provides an auction-based coordination mechanism that enables the allocation and pricing of service compositions in SVNs. The mechanism is multidimensional incentive compatible and implements an ex-post service level enforcement. Further extensions of the mechanism are evaluated following analytical and numerical research methods.
urn:nbn:de:0072-239751
Keywords: 330; Service Value Network; Service; Web Service; Auction; Game Theory; Dienstleistung; Unternehmensnetzwerk; Betriebliche Wertschöpfung; Dienstleistungsqualität; Auktion; Mechanismus-Design-Theorie; Theorie